Satisfaction with the Life of Neurogeriatric Patients - Mariusz Wysokiński; Barbara Kuszplak; Kamil Kuszplak; Wiesław Fidecki; Dorota Kulina; Monika Bieniak; Aneta Jędrzejewska; Agnieszka Kijowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The concept of life satisfaction means a multi-factorial assessment, which is based mainly on such two premises as: satisfaction with experienced years and satisfaction with the present life. When examining the satisfaction of a person’s life, certain aspects of existence, on the basis of which the individual makes the assessment based on individual criteria, are analyzed. Aim. The aim of the study was to assess the life satisfaction of elderly patients hospitalized in neurological wards. Material and Methods. The research was carried out in hospitals in the city of Lublin, in the departments of neurology. The study involved 102 older people. The youngest respondent was 65 and the oldest was 90 (average age 74.36±6.78). The research was carried out using the Satisfaction with Life Scale (SWLS). Results. The average result in the Satisfaction with Life Scale which the respondents obtained was 16.27±5.00. After converting the result into stens, 54.9% of respondents obtained low results (stens 1–4). 39.2% obtained average results (stens 5–6), and 5.9% high scores (stens 7–10). Conclusions. Self-evaluation of the life satisfaction of older patients in neurological wards was at a low level. The assessment of satisfaction with life significantly differentiated such variables as: sex, marital status, education, the fact of who the respondent lives with, and the place of residence. (JNNN 2018;7(4):145–149)